2002
DOI: 10.1002/pf.7
|View full text |Cite
|
Sign up to set email alerts
|

Race and gender differences in philanthropy: Indiana as a test case

Abstract: Rigorous economic research provides clear indications regarding the likelihood of volunteering and giving among demographic groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 28 publications
3
34
1
1
Order By: Relevance
“…Empirical studies are conclusive about the individual impact of educational level on the decision to volunteer. In fact, educational attainment is considered by some authors as the best predictor of volunteerism (Mesch, Rooney, Chin, & Steinberg, 2002;Gómez & Guntherson, 2003;Grønbjerg & Never, 2004;Musick & Wilson, 2008;Gesthuizen & Scheepers, 2012). However, we expect that the role of education in encouraging volunteerism itself depends on context.…”
Section: Socio-demographic and Contextual Forcesmentioning
confidence: 91%
See 1 more Smart Citation
“…Empirical studies are conclusive about the individual impact of educational level on the decision to volunteer. In fact, educational attainment is considered by some authors as the best predictor of volunteerism (Mesch, Rooney, Chin, & Steinberg, 2002;Gómez & Guntherson, 2003;Grønbjerg & Never, 2004;Musick & Wilson, 2008;Gesthuizen & Scheepers, 2012). However, we expect that the role of education in encouraging volunteerism itself depends on context.…”
Section: Socio-demographic and Contextual Forcesmentioning
confidence: 91%
“…Some studies indicate correlation between devotion to volunteering and marital status (Menchik & Weisbrod, 1987;Vaillancourt, 1994;Day & Devlin, 1996;Mesch et al, 2002;Nesbit, 2012). Menchik and Weisbrod (1987) find a higher rate of volunteering among married people, while Vaillancourt (1994) argues that single women do more volunteering than married women.…”
Section: Socio-demographic and Contextual Forcesmentioning
confidence: 99%
“…Minorities in this sample volunteered on average more hours than did Whites (169 to 126 h annually), yet this difference was not statistically significant. In fact, the survey found no statistically significant differences by race in volunteering or charitable giving [13].…”
Section: Researchmentioning
confidence: 98%
“…Although the targeted socio-economic class of donors, charitable causes, and countries and regions have been diverse in these studies, some patterns of effects of individual attributes and household compositions on the decision of charitable giving have been elucidated. The studies of socio-economic variables include economic status (Bell and Force 1956;Banks and Tanner 1999;Brooks 2002;Wang and Graddy 2008), income status (Hughes and Luksetich 2008;James and Sharpe 2007), educational attainment (Brown 1999), age (Pharoah and Tanner 1997;Gittell and Tebaldi 2006), marital status (Feldstein and Taylor 1976;Feenberg 1987;Andreoni et al 2003;Mesch et al 2006), sex (Kaplan and Hayes 1993;Hodgkinson and Weitzman 1986;Bulcroft et al 1996;Mesch et al 2002;Chrenka et al 2003), social class (Jones and Posnett 1991;McClelland and Brooks 2004), and race and ethnicity (Mesch et al 2002;Kaplan and Hayes 1993). Besides the physical and social attribute, experience of participation in prosocial activities such as volunteering (Simmon and Emanuele 2004), social norms (Piliavin and Charng 1990;Radley and Kennedy 1995), and perceptional and attitudinal factors such as trust and appreciation of government responsibility (Brooks 2003;Sargeant et al 2006;Matsunaga 2007) have all been shown to affect giving behavior.…”
Section: Previous Research and Research Questionsmentioning
confidence: 99%